Adaptive flow control in asynchronous transfer mode networks - Duan, Yanbing. (2008)
In this thesis, we present the results of research work on adaptive flow control in Asynchronous Transfer Mode (ATM) networks, which is base on Explicit Rate (ER) feedback control strategy recommended by ATM forum. Motivation of the adaptive flow control arises from the fact that ATM architecture design requires the efficient and fair use of the available network resource.